The efficacy of a network intervention to reduce HIV risk behaviors among drug users and risk partners in Chiang Mai, Thailand and Philadelphia, USA - Carl A. Latkin (2018)
This HIV Prevention Trials Network study assessed the efficacy of a network-oriented peer education intervention promoting HIV risk reduction among injection drug users and their drug and sexual network members in Chiang Mai, Thailand and Philadelphia, USA. The study was designed to test impact on HIV infection, but the infection rate was low and the study was terminated early. This paper reports efficacy on outcomes of self-reported HIV risk behaviors. We enrolled 414 networks with 1123 participants. The experimental intervention consisted of six small group peer educator training sessions and two booster sessions delivered to the network index only. All participants in both arms received individual HIV counseling and testing. Follow-up visits occurred every six months for up to 30 months. There were 10 HIV seroconversions, 5 in each arm. The number of participants reporting injection risk behaviors dropped dramatically between baseline and follow-up in both arms at both sites. Index members in the intervention arm engaged in more conversations about HIV risk following the intervention compared to control indexes. There was no evidence of change in sexual risk as a result of the intervention. Reductions in injection risk behaviors were observed: 37%, 20%, and 26% reduction in odds of sharing cottons, rinse water and cookers, respectively, and 24% reduction in using a syringe after someone else. Analysis of the individual sites suggested a pattern of reductions in injection risk behaviors in the Philadelphia site. In both sites, the intervention resulted in index injection drug users engaging in the community role of discussing reduction in HIV injection risk behaviors. The intervention did not result in overall reductions in self-reported sexual risk behaviors, and although reductions in injection risk behaviors were observed, the overall efficacy in reducing risk was not established. © 2008 Elsevier Ltd.